Magnetic field generation in PMS stars with and without radiative core. Issue Volume 12:Issue S328(2016) (12th September 2017) - Zaire, B.; Guerrero, G.; Kosovichev, A. G.; Smolarkiewicz, P. K.; Landin, N. R.
Abstract: Recent observations of the magnetic field in pre-main sequence stars suggest that the magnetic field topology changes as a function of age. The presence of a tachocline could be an important factor in the development of magnetic field with higher multipolar modes. In this work we performed MHD simulations using the EULAG-MHD code to study the magnetic field generation and evolution in models that mimic stars at two evolutionary stages. The stratification for both stellar phases was computed by fitting stellar structure profiles obtained with the ATON stellar evolution code. The first stage is at 1.1Myr, when the star is completely convective. The second stage is at 14Myrs, when the star is partly convective, with a radiative core developed up to 30% of the stellar radius. In this proceedings we present a preliminary analysis of the resulting mean-flows and magnetic field. The mean-flow analysis shown that the star rotate almost rigidly on the fully convective phase, whereas at the partially convective phase there is differential rotation with conical contours of iso-rotation. As for the mean magnetic field both simulations show similarities with respect to the field evolution. However, the topology of the magnetic field is different.